2011
DOI: 10.1097/coc.0b013e3181e1d0c0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia During Chemotherapy for Hematologic and Solid Tumors Is Correlated With Increased Toxicity

Abstract: In NHL patients, hyperglycemia correlates with NHemT, and a similar although less clear pattern is suggested in PC patients. Prospective studies are needed to assess whether a better glycemic control during chemotherapy can improve toxicity and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 37 publications
2
72
1
2
Order By: Relevance
“…In this view, Wang et al, (2000) reported a transient esophageal motor dysfunction with dysphagia in a 62-year-old man receiving vincristine-containing chemotherapy for nonHodgkin's lymphoma. As reported in a recent study by Brunello et al, 2011, a marginal increase in the glycemic levels were observed in the present study (Figure 9). Dysuria was a minor complaint in many and none had dysuria of grade 3 (Figure 10).…”
Section: Resultssupporting
confidence: 86%
“…In this view, Wang et al, (2000) reported a transient esophageal motor dysfunction with dysphagia in a 62-year-old man receiving vincristine-containing chemotherapy for nonHodgkin's lymphoma. As reported in a recent study by Brunello et al, 2011, a marginal increase in the glycemic levels were observed in the present study (Figure 9). Dysuria was a minor complaint in many and none had dysuria of grade 3 (Figure 10).…”
Section: Resultssupporting
confidence: 86%
“…Our documented prevalence of hyperglycemia (58.9%) is similar to other published values in cancer patients: for example, 58.1% in pediatric patients with all (97 of 167) 15 , 43.2% in patients with non-Hodgkin lymphoma (70 of 162), and 49.2% in prostate cancer patients (92 of 187) 27 .…”
Section: Discussionsupporting
confidence: 88%
“…Sample size was calculated conservatively assuming a prevalence of 40% for gc-induced hyperglycemia (based on published values derived from a cohort of non-Hodgkin lymphoma patients undergoing chemotherapy 27 ). Standard deviation was estimated higher (at 50%), given the large deviations in glucose previously reported in similar gc studies 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of these hormones and growth factors on multiple organs and sub-cellular systems (e.g., CNS and brain cognition, stem cells, mitochondrial function, neurogenesis and myelination, traumatic injury, wound healing responses) in reproductive and non-reproductive, immune and non-immune systems and their association in the development of chronic diseases or cancer have been the topic of extensive studies (Davis et al, 2011, Deng et al, 2008, Khatami 2009, Mikkola and Clakson 2002, Pisani 2008, Piatkliewicz and Czech 2011, Poulsen and Kruger 2006, Rauvala and Rouhianen 2001, Ren et al, 2009, Schwarts and Pashko 2004. For example, steroids or insulin play important roles not only in the function of reproductive organs and regulation of fluid homeostasis and/or metabolic pathways and immune responses to stress, but they are also involved in physiology, function and remodeling of bone, neuronal function, myelination and neurogeneration of brain and CNS and/or membrane-associated fatty acid metabolism (Bosch et al, 2002, Brunello et al, 2011, Campisi 2011, Chung et al, 2011, Goronzy and Wavand 2005, Hotamisisligil 2006, Khatami 1990, Li et al, 1986, Mikkola and Clarkson 2002, Sansoni et al, 2008, Simon and Balkau 2010, van Kruijsdijk et al, 2009). Insulin deficiency, insulin-resistance or hyper-insulinimia, or glucose toxicity and hyperglycemia of diabetes-induced increased glycosylation of proteins (advanced glycation end-products-AGE and their receptors RAGE) are associated with disturbances in transport and metabolism of important nutrients (e.g., ascorbic acid, pyridoxal phosphate, myo-inositol, etc), increased oxidative stress, accumulation of ROS, and co-expression of pro-and anti-inflammatory mediators such as NF-kB, VEGF, TNF-, IL1a, IL-6, IL-8, IL-12, and Ikappa B kinase (IKK-), platelets' CD40L, VCAM-1, in endothelial, hepatocytes or myeloid cells and/or tissues that are insulin-dependent (e.g., muscle, liver, adipocytes) or insulin-independent (e.g., vasculature, kidney, nerves, retina, RPE, lens) for glucose transport or metabolism , 1990, Li et al, 1986, Park et al, 2005…”
Section: Inflammation and Age-associated Diseasesmentioning
confidence: 99%